Oral Democracy Deliberation in Indian Village Assemblies - Sanyal, Paromita (Social Sciences, 2018)
A talk-centered qualitative analysis of three hundred Indian village assemblies, revealing how the deliberation between citizens in a mass democracy is influenced by state policy and literacy. Essential reading for those interested in participation, development, and deliberative democracy. This title is also available as Open Access.